The CABRI fast neutrons Hodoscope: CABRI model and signal-to-mass conversion charts - Chevalier Vincent; Di Salvo Jacques (EPJ Web of Conferences, 2023)
The CABRI experimental pulse reactor, located at the Cadarache nuclear research center, southern France, is devoted to the study of Reactivity Initiated Accidents (RIA). The hodoscope, installed in the CABRI reactor, is a unique online fuel motion monitoring system, operated by IRSN. This equipment is dedicated to the measurement of the fast neutrons emitted by the tested rod, in real time (with a rate of 1ms), during the power pulse. It is one of the distinctive features of the CABRI reactor facility, which is operated by CEA. To support the experimental task around CABRI reactor, by the experimenters who work on the Hodoscope, a Monte Carlo model, using the MORET code, is used by IRSN. This paper presents the main outcomes obtained during the reactor commissioning tests functioning, using Hodoscope results compared to MORET calculations, which proves the validity of the CABRI MORET model. Furthermore, we show how MORET code is used to build the signal-to-mass conversion charts of the Hodoscope.